Detailed biogeographical mapping as a useful novel tool for the conservation of endemic taxa: a case of study for Iberian orchids [version 2; peer review: 2 approved] - Angel Penas; Alejandro González-Pérez; Raquel Alonso-Redondo; Norma Yolanda Ochoa-Ramos; Aitor Álvarez-Santacoloma; Sara del Río; Giovanni-Breogán Ferreiro-Lera (Open Research Europe)
Background Many Iberian orchids occur in plant communities designated as habitats of interest in the European Union, particularly in Mediterranean grasslands and forests. Their ecological importance highlights the need for a deeper understanding of their distribution and ecological requirements in order to develop effective conservation and management policies. Methods This study focuses on the biogeographical mapping and characterisation of five Iberian and Balearic endemic orchid species at district level. Distribution data were collected from existing biodiversity databases and integrated into a Geographic Information System (GIS). In order to assign the correct biogeographical epithet to each taxon, a set of rules and criteria was developed to ensure an objective, simple and universal classification based on the species' distribution areas. Results For each orchid species, the study identified its phytosociological assignment, bioclimatic range and current conservation status. Detailed maps were produced, providing insights into the biogeographical, bioclimatic and phytosociological attributes of these taxa. Conclusions The biogeographical mapping and ecological classification presented in this study provide a basis for effective decision-making regarding the conservation and management of these orchid species. In addition, the results can be used to update their conservation status to better reflect their ecological needs and threats.